Estudio de factibilidad para la implementación de un aerogenerador para generación de energía eléctrica en la zona de Cayambe - Lechón Necpas, Edwin Cesar (2016)
The following titling project analyzes the feasibility of the implementation of a wind turbine for generating electricity, and also it wants to evaluate the possibility of its use in the community La Chimba parish in Olmedo - Cayambe, Pichincha Province. This research tries to contribute to the solution for electricity problem in this sector, taking advantage of the high-speed wind that exists in this area. The subsequent project clarifies a brief explanation of the history, evolution, characteristics climate, demand, maximum and minimum installation requirements as well as the advantages and disadvantages of renewable energy. The community La Chimba presents electricity deficit due to blackouts and the cost of the electricity payrolls. For these reasons, this research looks for new alternatives of electricity, which are friendly with the environment and accessible for the community of this parish. During the investigation it was selected the best alternative wind turbine, which satisfied all needs, trying to reduce installation and operating costs. Moreover, the wind turbine must be accessible to the economy of the town. If the result of this research shows feasibility the electricity problems in La Chimba parish would be solved. The wind turbine could provide energy to enough homes and many people would be benefited because their business will increase, as well as their economy. Beyond to be a common research, this work tries to give sufficient technical information to implement the application of a wind turbine in La Chimba in Cayambe.